Implementasi Sistem Pendukung Keputusan Menggunakan Algoritma MOORA untuk Pemilihan Jenis Bibit Cabai Unggul - Al Akbar, Abdussalam; Yasin, Alimuddin; Alex Rizky Saputra; Sepriano; Siregar, Ratu Mutiara; Budy Satria; Elfitra (The Indonesian Journal of Computer Science, 2023)
Cultivating chili plants is a business opportunity that has quite a large income. However, many farmers still use traditional concepts in determining which seeds to plant, such as trying out chili seeds without carrying out in-depth analysis or observation. A decision support system (DSS) is a system that is capable of providing decision recommendations using several criteria determined through method processes in the decision making system, namely ARAS, SAW, MOORA, AHP and others. The MOORA method is useful for separating the subjective part of an evaluation process into a decision weight criterion with several decision making attributes. And also the level of selectivity of this method is very good because it can determine objectives from conflicting criteria. Where the criteria can be profitable (benefit) or unprofitable (cost). Based on the results obtained after using the MOORA calculation method, there are 4 types of superior seed varieties that can be recommended for farmers, namely Taro Chili Seeds = 0.2875; Indrapura Chili Seeds = 0.2595 ; Lado Chili Seeds = 0.2490 ; Chili Seeds TM = 0.2154. By creating this decision support system, it is hoped that farmers will be able to use it as a reference in selecting superior chili seeds and be able to get maximum harvest results and increase commodity income for chili farmers.